Clustering of risk factors for abdominal obesity in Turkish adults and its demographic distribution - Onat, Allan; Uyarel, Huseyin; Karabulut, Ahmet; Albayrak, Sinan; Dogan, Yuksel; Can, Gunay; Hergenc, Gunay; Sansoy, Vedat (TURKISH SOC CARDIOLOGY, 2005)
Objectives: We investigated the distribution of abdominal obesity among Turkish adults, according to age groups and geographic regions, and the prevalence and type of its clustering with traditional risk factors including high total and low HDL cholesterol levels, smoking, hypertension, and diabetes. Study design: The study included a cohort of 3267 individuals (1607 men, 1660 women; mean age 52 +/- 12 years) whose waist circumferences were measured at least one time in the past three surveys of the Turkish Adult Risk Factor Study from 2000 to 2004. Cardiovascular disease was diagnosed on the basis of the presence of angina history, the Minnesota coding of resting electrocardiograms, and a history of stroke. Criteria of the NCEP ATP III guidelines proposed for metabolic syndrome were adopted for defining abdominal obesity and hypertension. Results: Out of every four adults aged 50 years or above, one man and three women had abdominal obesity. The prevalence of abdominal obesity did not exhibit marked changes among geographic regions. Coexistence of 3-5 risk factors in subjects with abdominal obesity showed a significantly higher proportion than other clusters of risk factors (p = 96 cm, which was previously proposed by the authors.
Keywords: Abdomen; coronary disease; diabetes mellitus; female; hypercholesterolemia; hypertension; lipoproteins; HDL cholesterol; obesity; risk factors; Cardiovascular System & Cardiology